Diarrhea and enteric emerging viruses in HIV-infected patients - Giordano, M O; Martinez, L C; Rinaldi, D; Espul, C; Martinez, N; Isa, M B; Depetris, A R; Medeot, S I; Nates, S V (AIDS research and human retroviruses, 1999)
To evaluate the prevalence of enteric viruses and their possible association with diarrhea, 244 stool samples were collected from HIV-infected and uninfected patients with or without diarrhea (subgroups I-a, Ib, II-a, and II-b, respectively). Subjects were screened by polyacrylamide gel electrophoresis, latex agglutination, and enzyme immunoassays for rotaviruses, adenoviruses, picobirnaviruses, and astroviruses. Enteric viruses were found significantly more often in specimens from HIV patients (20%) than in specimens from uninfected HIV patients (0%) (p < 0.05). Picobirnavirus was detected in 14.63% of 82 HIV-infected patients with diarrhea, but it was detected neither in those without diarrhea (0%) (p < 0.05) nor in the groups of uninfected HIV subjects (0%) (p < 0.05). Nor could astrovirus (subgroups I-a [4.00%] versus subgroup I-b [5.26%],p > 0.05) or enteric adenovirus (subgroup I-a [1.22%] versus subgroup I-b [0%], p > 0.05) be linked to the diarrhea disorder in HIV-infected patients. Rotaviruses were not detected in any of the clinical subgroups studied. Enteric viruses were detected in 15 of 93 (16.13%) of the HIV-infected patients with CD4+ T cell count <200/microl and 3 of 19 (15.79%) of those HIV-infected individuals with a CD4+ T cell count 200-499/microl, showing no significant difference (p > 0.05). According to our data, unusual enteric viruses such as picobirnavirus, astrovirus, and enteric adenovirus occur in HIV-infected population in Córdoba, Argentina. However, only picobirnaviruses could be significantly associated with diarrhea in these patients.